ClimKern v1.2: a new Python package and kernel repository for calculating radiative feedbacks - T. P. Janoski; T. P. Janoski; T. P. Janoski; T. P. Janoski; T. P. Janoski; I. Mitevski; R. J. Kramer; M. Previdi; L. M. Polvani; L. M. Polvani; L. M. Polvani (Geoscientific Model Development)
Climate feedbacks are a significant source of uncertainty in future climate projections and need to be quantified accurately and robustly. The radiative kernel method is commonly used to efficiently compute individual climate feedbacks from climate model or reanalysis output. Despite its popularity, it suffers from complications, including difficult-to-locate radiative kernels, inconsistent kernel properties, and a lack of standardized assumptions in radiative feedback calculations, limiting the robustness and reproducibility of climate feedback computations. We designed the ClimKern project to address these issues with a kernel repository and a separate but complementary Python package of the same name. We selected 11 sets of radiative kernels and gave them a common nomenclature and data structure. The ClimKern Python package provides easy access to the kernel repository and functions to compute feedbacks, sometimes with a single line of code. ClimKern functions contain helpful optional parameters while maintaining standard practices between calculations.